2020
DOI: 10.1101/2020.05.11.089318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Basis for N-terminal Alpha-Synuclein Acetylation by Human NatB

Abstract: NatB is one of three major N-terminal acetyltransferase (NAT) complexes (NatA-NatC), which co-translationally acetylate the N-termini of eukaryotic proteins. Its substrates account for about 21% of the human proteome, including well known proteins such as actin, tropomyosin, CDK2, and αsynuclein (aSyn). Human NatB (hNatB) mediated N-terminal acetylation of αSyn has been demonstrated to play key roles in Parkinson's disease pathogenesis and as a potential therapeutic target for hepatocellular carcinoma.Here we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 79 publications
(117 reference statements)
1
8
0
Order By: Relevance
“…Inositol hexaphosphate (IP6) binding contributes to yeast NatC complex stability. Earlier reports demonstrated that IP6 interacts with and stabilizes both the yeast and human NatA and NatE complexes (Cheng et al, 2019;Deng et al, 2019;Deng et al, 2020a;Gottlieb and Marmorstein, 2018), but does not appear to interact with human NatB (Deng et al, 2020b). To determine if IP6 could bind to the recombinant NatC complex, we employed isothermal titration calorimetry (ITC).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Inositol hexaphosphate (IP6) binding contributes to yeast NatC complex stability. Earlier reports demonstrated that IP6 interacts with and stabilizes both the yeast and human NatA and NatE complexes (Cheng et al, 2019;Deng et al, 2019;Deng et al, 2020a;Gottlieb and Marmorstein, 2018), but does not appear to interact with human NatB (Deng et al, 2020b). To determine if IP6 could bind to the recombinant NatC complex, we employed isothermal titration calorimetry (ITC).…”
Section: Resultsmentioning
confidence: 99%
“…While Naa30 displays a canonical NAT fold with mixed α/β secondary structure, the Naa35/38 complex forms a clamp that pinches Naa30 on opposite sides. This clamp-like structure is distinct from the architecture of the large auxiliary subunits of NatA and NatB, which surround the base of their respective catalytic subunits (Deng et al, 2020b;Gottlieb and Marmorstein, 2018;Hong et al, 2017;. The Naa35 architecture is mostly helical, with 25 helices, three short β-strands in its N-terminal region and a single β-hairpin at its C-terminal region that are unique to the NatC complex (Figure 2b and Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations